Development of Ad Videos as Instagram Reels Content Using the Adobe Premiere Pro Application at PT. Air the Best Langga, Kepanjen Branch - Mujahidah, Aulia Miftakhul; Rochman, Fatkhur; Pribadi, Joni Dwi (Transpublika Publisher, 2024)
The existence of the internet and digital technology has changed the way companies interact with customers. This shift has opened up huge opportunities for promotions, allowing businesses to connect with their audiences more easily and effectively. This research aims to develop Instagram reel ad videos using Adobe Premiere Pro for PT. Air The Best Langga, Kepanjen branch office. This research was action research. The data collection was conducted by observation, interviews, questionnaires, and documentation. The EPIC model was employed to analyze the effectiveness of the videos to determine their feasibility for posting on Instagram reels. The research unit comprised 2 marketing experts, 2 computer experts, 1 company owner, and 10 consumers. The results showed that the advertising video fell into the highly effective category, with a calculated score of 4.54 for the overall EPIC rate average. This indicated that the video was suitable for publication. The conclusion obtained from this research is that the advertising videos are feasible to use and can be published as advertising media for PT. Air The Best Langga, Kepanjen branch. It is expected that the company can use the video as an advertising medium on its Instagram account. The company also has to monitor and maintain posts, and keep up with trending updates on Instagram.